Composite structures of steel and concrete : beams, slabs, columns, and frames for buildings - Johnson, R. P. (Blackwell Pub., 2004)
This book provides an introduction to the theory and design of composite structures of steel and concrete. Material that is applicable to both buildings and bridges is included, plus more detailed information relating to buildings. Throughout, the design methods are illustrated by calculations in accordance with the Eurocode for composite structures. The methods are stated and explained, so that no reference to these new design codes is needed. --